Impact of severity and therapy onset on helmet therapy in positional plagiocephaly - Freudlsperger, Christian; Steinmacher, Sahra; Saure, Daniel; Bodem, Jens; Kühle, Reinald; Hoffmann, Jürgen; Engel, Michael (Journal of cranio-maxillofacial surgery, 2016)
Although helmet therapy is a widely established method in the treatment of positional plagiocephaly, therapeutic regimens remain contentious, especially regarding starting age. Hence, this study investigated the impact of starting age and severity on the effectiveness of helmet therapy. A total of 213 pediatric patients treated for positional plagiocephaly with an orthotic device were enrolled in this study. Pre- and post-treatment calvarial asymmetry was measured according to the Cranial Vault Asymmetry Index (CVAI) using 3D-Photogrammetry. Patients were classified by age at which treatment was started: Group 1 was comprised of patients younger than 24 weeks (n = 82); Group 2, those aged 24-32 weeks (n = 75); Group 3, those aged >32 weeks (n = 56). Additionally, groups were categorized by severity (mild: CVAI 3-7%; moderate: CVAI 7-12%; severe: CVAI > 12%). Mean initial CVAI was 9.8%, which reduced to 5.4% after helmet treatment. Group 1 (<24 weeks) showed the highest absolute and relative rate of correction. Within the groups, severity correlated positively with relative and absolute reduction of the asymmetry. A significant difference in the reduction of the CVAI depending on age was only seen in moderate and severe cases of plagiocephaly- but not in mild plagiocephaly. The present study confirms the effectiveness of helmet therapy for positional plagiocephaly. The use of an orthotic device is an appropriate treatment option particularly in infants with severe plagiocephaly and a start of helmet therapy before the age of 6 month is advisable.
Available online 8 December 2015
Gesehen am 27.05.2020